Maria Montessori et la diffusion de la pédagogie montessorienne aux États-Unis (1910-1920) - Sébastien-Akira Alix (Recherches en Éducation)
This article explores the dissemination of Montessorian pedagogy in the United States between 1910 and 1920, whose history is little known to the French readership. In a transnational perspective, this article examines the first transatlantic circulations of Montessorian pedagogy in America, highlighting the emergence and consolidation of social networks that contributed to the rise of Maria Montessori's educational ideas and practices in the United States. The article also contains explanation of the reasons for the failure of the implementation of Montessori education in the U.S. until the movement’s re-emergence in the 1950s.